The emergence of a “City of Cages” in Lima: neighbourhood appropriation in the context of rising insecurities - Jörg Plöger (Unité Mixte de Recherche 8504 Géographie-cités, 2007)
Lima, like other Latin American metropolises, has experienced profound changes in the context of broader transformation processes since the 1990s. Gated residential developments have emerged as one characteristic feature of the new spatial order. The Peruvian capital shows some unique features however. “Typical” gated communities are relatively seldom. Subsequently enclosed neighbourhoods are the dominant type of residential enclave and the main focus of this article. They have now spread across most parts of the metropolitan area and crosscut socio-economic lines. Security-related interventions such as the installation of street gates or the employment of security guards are implemented subsequently. Further characteristics are the high degree of informality and the dominant role of the residents in local place building. This article analyses different aspects of the fortification process in Lima, such as its dimension, factors shaping the spatial outcome, the interaction with other security-providing bodies and the importance of residential organisation.It will be argued that their emergence must be understood in the context of wider transformation processes related to the recession of the 1980s and structural adjustment of the 1990s. The majority of the population is confronted with a wide range of insecurities. These are most directly expressed through a perceived or real increase in crime and anti-social behaviour. The state, on the other hand, seems to be unable to provide sufficient services. In the realm of security provision this is manifested in the proliferation of additional actors. As a consequence of the “protection gap”, the residents of many areas in Lima have reacted by continuously appropriating, controlling and fortifying their neighbourhoods. This exertion of localised spatial control can be interpreted as an attempt to re-establish stable “comfort zones” as opposed to wider urban social divisions.